Main musculoskeletal complaints by musicians in the ABC Paulista region: a prevalence study - Reijani, Nádia; Benetti, Fernanda Antico (ABCS Health Sciences, 2016)
Introduction: Musicians are professionals with several predisposing factors to developing the occupational illness. Most of the time, they present serious complaints. Awareness of the musician to the risks that he may suffer and methods of prevention are essential to prevent further damage that might prevent the practice of activity that the trader carries, since music is related to well-being, emotional balance and fun. Objective: Collect data and analyze what are the main musculoskeletal complaints of musicians due to posture acquired instrumentalist practice. Methods: The sample contained 80 musicians, students and professionals of the Associação Cultural Tocando a Vida, Big Band da Fundação das Artes de São Caetano do Sul and the Orquestra Sinfônica da Fundação das Artes de São Caetano do Sul. These musicians have gone through a screening and after answered the questionnaire Nordic Musculoskeletal. Results: It was observed that for all the instruments of half or more families have pain caused by the practice instrumentistal. Conclusion: It can be concluded that the regions of hands and lumbar spine were the places most affected by the practice of instruments. It was not possible to analyze and relate the prevalence of musculoskeletal injuries on the musicians, because the vast majority did not perform medical care and had no clinical diagnosis.